An Experimental investigation of Sustainable Concrete by incorporating E-waste and Fly Ash. (2022) - Sharma, Neha; Sharma, Prashant; kumar Parashar, Arun
Abstract: Nowadays, recycling of electronic waste (E-waste) is a tremendous issue due to rapid growth of IT sector. This E-waste can cause several hazards to human health. In this investigation, fly ash was substituted for cement and E-waste fibres were added to concrete, which was tested for its mechanical properties. E-waste fibres have been incorporated to increase the mechanical strength and to reduce the cracks in the concrete specimens. Concrete samples of M30 grade had made by replacing 5, 10, and 15 percentages of cement with fly ash. Various experimental tests have been conducted with different proportion of fly ash and E-waste fibre. There was a percent increase in mechanical strength after E-waste replacement. The flexural strength of the concrete beams improved by some amount with the largest increase in flexural strength obtained for the FA10%. The results of the study demonstrated that the employment of EW and FA in the manufacture of concrete as a partial replacement for cement can result in the development of more durable concrete with high strength.